1992
DOI: 10.1111/j.1475-097x.1992.tb00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtraction of extra‐renal background in 99mTc‐DTPA renography: comparison of various regions of interest

Abstract: Quantitative evaluation of renal function in 99mTc-DTPA isotope renography is hampered by high background activity. This study compares various background regions of interest (ROIs) to obtain the most accurate estimate of the extra-renal background, taking both total counts (integral value) and change by time (slope) into account. Gamma camera renography was performed in 21 patients with a single kidney. Time-activity histograms obtained from 8 different background ROIs were compared in the time interval corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…A unified method of DRF calculation and background ROI type and placement was, in our case, achieved by using the same processing software, which the observers were used to. An integral method was used for DRF calculation and perirenal ROI [21][22][23] was used for background subtraction; both methods were validated with respect to reproducibility [13] and are recommended by guidelines [1][2][3][4]. As both methods are routinely used at our institution and our goal was to assess reproducibility of our routine work, alternative methods of background subtraction and DRF calculation were not used in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A unified method of DRF calculation and background ROI type and placement was, in our case, achieved by using the same processing software, which the observers were used to. An integral method was used for DRF calculation and perirenal ROI [21][22][23] was used for background subtraction; both methods were validated with respect to reproducibility [13] and are recommended by guidelines [1][2][3][4]. As both methods are routinely used at our institution and our goal was to assess reproducibility of our routine work, alternative methods of background subtraction and DRF calculation were not used in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To correct for this directly requires a heart ROI plasma curve, of standard size and consistent placement, in itself a source of error. 'y, 20,26 The regression equation used to predict GFR may be different in each laboratory. ' A 99"Tc-DTPA labeling efficiency may vary from one laboratory to the other.…”
Section: Slope Uptake (Cps/s/ioo Mbq Injected)mentioning
confidence: 99%
“…Manually drawing the background ROI is common, with many methods of placing the ROI. A circumferential background ROI has been found to be the most reliable, 8,24 and in normal dogs its position and width caused considerable differences in percent uptake and accuracy 7 . Manual background ROI drawing is likely to introduce more variation.…”
Section: Discussionmentioning
confidence: 99%
“…Overcorrection or undercorrection of background activity will cause errors in the calculated percentage uptake of DTPA. Many different regions have been used in humans to represent background activity, 8,12,13 the perirenal being one of the most accurate 8 . With the 64 × 64 matrix size of the dynamic study, we found in normal dogs that a perirenal background ROI at one pixel out from the kidney ROI gave the best correlation between percentage uptake and GFR by plasma clearance, with both manual ROI and semi‐automatic ROI 7 …”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation